379 Prescription drug overdose: environmental and behavioural risks in homes with and without children. (1st September 2016) - Gielen, Andrea; McDonald, Eileen; Shields, Wendy; Kennedy-Hendricks, Alene; McGinty, Beth; Barry, Colleen
Abstract : Background: According to a UN panel, prescription drug abuse will soon exceed illicit drug use worldwide. In the US, opioid pain relievers (OPRs) are widely available, and overdose deaths have increased. Children are vulnerable to either or both unintentional and intentional exposure to OPRs. Little is known about the environmental and behavioural risks associated with storage and disposal of these drugs in homes with children. Methods: We addressed this gap by completing an on-line survey of a nationally representative sample of 1, 032 adults who had taken an OPR within the year preceding the survey. Environmental and behavioural risks examined by the presence and ages of children in the home were characteristics of the product, storage location, disposal plans and practices, and beliefs about safe storage. Results: One-third of the sample had children younger than 18 living in the home; 47% were still using the OPR at the time of the survey. Homes with children compared to those without were significantly more likely to have a child resistant cap on the medication (91% vs 78%) and to store the OPR most often in a place that was locked or latched, although the rates were low in both groups (27% vs 17%). Almost 40% of those who were no longer using the medication reported keeping it for future use, and only 5% reported turning the pills in to a take-back program. When asked about storage behaviours, adults with young children compared to those with older children/teens were significantly more likely to have positive beliefs about the benefits and higher perceived threats, and to report fewer barriers to safe storage. Conclusions: The high rates of unsafe storage and disposal of OPRs in homes with children is alarming because of the associated risks of unintentional or intentional exposure of children to these dangerous medications. Campaigns that focus on the risks to older children/teens and increasing the availability of take-back programs in communities are urgently needed.